Information technology and competitive advantage in small firms - Webb, Brian; Schlemmer, Frank (London ; New York : Routledge, 2008)
This book attempts to bridge the flow of strategic management literature, information technology literature and small firm literature, using economic and management theory to construct a vantage point from which management researchers and managers may more clearly see the currents that carry them along.
Includes bibliographical references (p. [150]-172) and index.
osc 30/04/13
Loan
Keywords: Information technology -- Management; Small business -- Management